Solitary plexiform neurofibroma, a pitfall in diagnosis of lipoma. (21st September 2010) - Chieng, G H; Bhatnagar, A; Mirza, M
Abstract : Plexiform neurofibromatosis is almost invariably associated with neurofibromatosis type I. A case of an isolated back plexiform neurofibroma, initially thought to be a lipoma, is presented, with emphasis on the importance of eliciting family history in reaching a diagnosis of neurofibromatosis. Currently, surgical resection is still the treatment of choice though a management plan is not well defined. Patients need appropriate regular follow-up to detect malignancy or early recurrence.